Effects of Stabilised Nitrogen Fertilizers in Oilseed Rape (Brassica napus L.) Nutrition - Dominika Mikusova; Pavel Ryant (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2021)
The aim of this study was to evaluate the effects of added nitrification inhibitor (NI) and urease inhibitor (UI) to urea ammonium nitrate (UAN) on oilseed rape yield and seed oil content in 3-year field trials and to assess their environmental impact by analysing the content of nitrates in water extracts in the form of soil laboratory experiments. The UAN stabilisation was provided by the addition of PIADIN (1.5% methylpyrazole, 3% triazole) serving as NI and StabilureN (NBPT) used as UI. The experiment consisted of four variants: 1. UAN; 2. UAN + NI; 3. UAN + UI; 4. UAN + NI + UI. The obtained data showed the increased rates of the yield and seed oil content in the variants with the NI/UI additions in one experimental year. Statistically significant differences were detected in the yield and seed oil content obtained between the years of the experiment. Soil laboratory experiments proved that the additions of both inhibitors (UAN + NI + UI) led to the least leaching of nitrates.